(untitled) (Bangladesh Critical Care Journal, 2019)
Background: A well-functioning vascular access (VA) is essential to provide efficient hemodialysis (HD) therapy. There are 3 main types of access: arterio-venous fistula (AVF), arterio-venous graft (AVG) and central venous catheter (temporary or permanent). The aim of our study was to find vascular access profile of ESRD patients on maintenance hemodialysis in a tertiary care hospital. Methods: This cross-sectional study was carried out in the Department of Nephrology and Dialysis of BIRDEM General Hospital, Dhaka, Bangladesh from November to December, 2015. After taking informed consent from the patients, data were collected from face to face interview and record books of the patients. Results: Total patients were 107, male were 78 (72.9 %) and female were 29 (27.1%). The mean age was 57.3 ± 11.4 (range 32-80) years. Mean duration of CKD was found 5.7 ± 4.2 (range 1-20) years. Maximum dialysis duration was 6.5 years with mean of 1.7 ± 1.3 years. Near two-thirds (68.2%) of the patients were on thrice-weekly dialysis and one-third (31.8%) were on twice-weekly dialysis. The vascular access at initiation of dialysis was temporary catheter in majority (91.6%) of study participant and AV fistula in 8.4% cases. Of temporary catheter one-third (33.7%) were temporary jugular catheter and two-third (66.3%) were temporary femoral catheter. Among jugular catheter 9.1% were left sided catheter and rest (90.9%) were right sided catheter. Among the femoral catheter 70.8% and 29.2% were right and left side respectively. The current vascular access was AV fistula in 90.7%, temporary catheters 4.7%, permanent catheter 3.7% and AVG 0.9% in study patients. Of AVF near one third (29.9%) were radio-cephalic and 70.1% were brachial (62.6% brachio-cephalic, 7.5% brachio-basilic) fistulas. About seventeen percent (16.8%) patients had AVF failure. Conclusion: Temporary dialysis catheters were the most common initial vascular access. Less than one-tenth patients started dialysis with AV fistula. More than two-thirds patients were on thrice weekly dialysis. AV fistula was the most common current vascular access with very small number of permanent catheter and AV graft. Bangladesh Crit Care J March 2019; 7(1): 26-28